Comparing political journalism - Vreese, C. H. de; Esser, Frank; Hopmann, David Nicolas (Routledge, 2017)
Comparing Political Journalism is a systematic, in-depth study of the factors that shape and influence political news coverage today. Using techniques drawn from the growing field of comparative political communication, an international group of contributors analyse political news content drawn from newspapers, television news, and news websites from 16 countries, to assess what kinds of media systems are most conducive to producing quality journalism. Underpinned by key conceptual themes, such as the role that the media are expected to play in democracies and quality of coverage, this analysis highlights the fragile balance of news performance in relation to economic forces. A multitude of causal factors are explored to explain key features of contemporary political news coverage, such as Strategy and Game Framing, Negativity, Political Balance, Personalization, Hard and Soft News Comparing Political Journalism offers an unparalleled scope in assessing the implications for the ongoing transformation of Western media systems, and addresses core concepts of central importance to students and scholars of political communication world-wide.